2020
DOI: 10.2478/hukin-2019-0098
|View full text |Cite
|
Sign up to set email alerts
|

How do Amateur Endurance Runners Alter Spatiotemporal Parameters and Step Variability as Running Velocity Increases? A Sex Comparison

Abstract: This study aimed to analyse the effects of running velocity on spatiotemporal parameters and step variability in amateur endurance runners, according to sex. A group of 51 males and 46 females performed an incremental running test on a treadmill (10-16 km/h). Spatiotemporal parameters (contact and flight time, step length, step frequency and step angle [CT, FT, SL, SF, SA]) and step variability, in terms of within-participant standard deviation (SD), were recorded through the OptoGait System. The ANOVA showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 31 publications
4
26
0
Order By: Relevance
“…In addition, CT has been linked as a determinant of leg stiffness, with higher values of leg stiffness associated with shorter CT [61]. The increase in stride angle was also observed at a higher rate, agreeing with those obtained in previous studies [43,60].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, CT has been linked as a determinant of leg stiffness, with higher values of leg stiffness associated with shorter CT [61]. The increase in stride angle was also observed at a higher rate, agreeing with those obtained in previous studies [43,60].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding adaptations of spatiotemporal parameters after the increase in velocity, the results of this study reinforced the findings of previous studies [43,59,60]. Increased running speed has been shown to lead to a reduction in CT (to facilitate the progression of the leg during the oscillation phase to a new contact [59]) and to an increase in step frequency, as a spatiotemporal adaptation needed to run faster [61].…”
Section: Discussionsupporting
confidence: 88%
“…Firstly, only male Japanese endurance runners were recruited; therefore, the findings cannot be generalized to include runners of other races or other genders. A previous study has reported differences in step characteristics between male and female endurance runners [ 29 ]. Previous studies have also reported race-related differences in step characteristics based on morphological variations [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SL of two gait cycles on each lap was averaged. The mean coefficient of variation ± SD of SL for each lap was 1.7 ± 0.4%, and SL was normalized to body height (BH) to minimize the effect of body size [ 2 , 29 ]. Moreover, the instantaneous running speed (m/sec) was calculated by multiplying SF by SL.…”
Section: Methodsmentioning
confidence: 99%
“…31 The parameters obtained were; contact time (CT), and its three subparts, landing time (from the footstrike until the whole foot is in contact with the ground), midstance time (from when the whole foot is in contact until the heel is off the ground), propulsive time (from the moment the heel is off the ground until the foot is completely off the ground). In addition, flight time (FT), step length (SL), and cadence were recorded, which were previously defined by García-Pinillos et al 32…”
Section: Materials and Testingmentioning
confidence: 99%